EFFECT OFMULTI NUTRIENT BLOCKSUPPLEMENTATION TO LOCAL FEMALE RABBITS PERFORMANCE (Lepus negricollis) - I G. D. A., Wiguna; Nuriyasa, I M.; Puger, A. W. (Jurnal Peternakan Tropika, 2017)
This study aims to determine the effect of Multi Nutrient Block (MNB) supplementation on the performance of local female rabbits given ground grass feedstock. A randomized block design with four treatments and five blocks as replicates was used in this study, the treatment was a local female rabbit fed field grass onlyas control (R0), a control feed supplemented by MNB 15 g/head/day (R1), a control feedsupplemented MNB 30 g/head/day (R2), control feedsupplemented MNB 45 g/head/day (R3). The observed variabel wasl body weight, weight gain, grass consumption, MNB consumption, total consumption, energy consumption, crude protein intake, and feed conversion. The results showed that the higher the supplementation of MNB, the higher the final body weight, weight gain, MNB consumption, total consumption, energy consumption, and consumption of crude protein but reduced grass consumption compared with treatment without MNB supplementation (R0). It can be concluded that increasing multi nutrient block supplementation from 15g/head/day to 45g/head/day results in the performance of local female rabbit (Lepus nigricollis) also increased. Keywords: Performances, rabbit, multi nutrient block, field grass